Habib Ali bin Abdurrahman Alhabsyi Kwitang: Kontribusi Sosial Keagamaan dan Perjuangan Nasionalisme, 1889–1968 - Marpaung, Ira Fitri Lestari; Siregar, Yusra Dewi; Syam, Abdi Mubarak (Medan Resource Center, 2025)
This research investigates the historical and religious significance of Al-Habib Ali bin Abdurrahman Al-Habsyi Kwitang (1889–1968) in the context of Indonesia’s struggle for independence and the dissemination of Islamic teachings. The central question addresses how Habib Ali contributed to both the national movement and Islamic socio-religious development. Using the historical method, the study follows four stages: heuristic data collection, source criticism, interpretation, and historiographical synthesis. Findings indicate that Habib Ali played a critical role in advancing Islamic education by founding institutions such as Unwanul Falah and ICI, and was actively involved in religious-political organizations, notably the Majelis Islam A'la Indonesia (MIAI). His influence extended into national politics as a spiritual advisor to key leaders, including President Soekarno. The study concludes that Habib Ali’s legacy exemplifies the intertwined relationship between Islamic scholarship and nationalist discourse, reinforcing the prominent role of ulama in shaping Indonesia’s socio-political fabric and contributing to the broader intellectual tradition of Islam Nusantara.